ChemInform Abstract: Carbon—Carbon Bond Formation via Benzoyl Umpolung Attained by Photoinduced Electron‐Transfer with Benzimidazolines. Issue 15 (15th April 2014) - Igarashi, Tomohito; Tayama, Eiji; Iwamoto, Hajime; Hasegawa, Eietsu
Abstract It is proposed that electron transfer from a benzimidazoline additive to photoexcited benzoyl compounds (I) generates carbanions which react with alkyl halides to give alkylated alcohols.